Pathways of Pelagic Connectivity: Eukrohnia hamata (Chaetognatha) in the Arctic Ocean - DeHart, Hayley M.; Blanco-Bercial, Leocadio; Passacantando, Mollie; Questel, Jennifer M.; Bucklin, Ann (Frontiers in Marine Science, 2020)
The dramatic warming of the Arctic Ocean will impact pelagic ecosystems in complex ways, including shifting patterns of species distribution and abundance, and altering migration pathways and population connectivity. The Phylum Chaetognatha (arrow worms) are abundant in the zooplankton assemblage and are highly effective predators, with key roles in pelagic food webs. They are useful indicator species for impacts of climate change on marine ecosystems. This study examined the population genetic diversity, structure and connectivity of the chaetognath, Eukrohnia hamata, based on sampling from six regions defined by geography, bathymetry, and major currents flowing through the Arctic Ocean. A 650-bp region of mitochondrial cytochrome oxidase I (mtCOI) sequenced for 130 specimens resulted in 78 haplotypes and very high haplotype diversity. Analysis of mtCOI haplotype frequencies provided no evidence of population genetic structure. Genomic Single Nucleotide Polymorphisms (SNPs) detected from the same specimens by double-digest Restriction-Associated Digestion (ddRAD) confirmed high levels of gene flow among the regions, but supported the genetic distinctiveness of two population clusters: Atlantic-Arctic versus Pacific-Arctic. Removal of SNPs subject to selection resulted in slightly higher probability of three clusters, and suggested the possibility of local adaptation of regional populations of E. hamata. Comparative analysis revealed evidence that random selection of subsets of SNPs, perhaps impacted by different ecological and (micro) evolutionary drivers, can result in marked differences in numbers and distributional patterns of clusters and associated variation in F-statistics. Analysis of population connectivity using SNPs supported the primary migration pathway via flow from the Atlantic to the Pacific Arctic regions.